2022
DOI: 10.3390/ijerph192416449
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biodegradation of BTEX in the Subsurface of a Petrochemical Site near the Yangtze River, China

Abstract: The contamination of soil and groundwater with BTEX (benzene, toluene, ethyl benzene, and xylenes) is a common issue at petrochemical sites, posing a threat to the ecosystems and human health. The goal of this study was to evaluate the biodegradation of BTEX in the subsurface of a petrochemical site near the Yangtze River, thus providing scientific basis for bioremediation of the contaminated site. Both molecular analysis of field samples and microcosm study in the laboratory were performed for the evaluation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Aerobic degradation is often more efficient than anaerobic (Tarasov et al, 2004;Kauppi et al, 2011), encouraging the addition of oxygen as a gas straight into the soil or the aquatic phase (Penttinen, 2001), or as a breakdown product of chemicals such as peroxide, persulfate, ozone or permanganate (Tarasov et al, 2004;Goi et al, 2006;Yen et al, 2011;Nykänen et al, 2012;Simpanen et al, 2016a;Bajagain et al, 2018Bajagain et al, , 2020b. The dissolvability of oxygen is comparatively low; alternatives like nitrate and sulfate sidestep this problem but come with a heightened risk of groundwater pollution (Chen et al, 2022).…”
Section: Microbial Bioremediation -Forms Prerequisites and Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerobic degradation is often more efficient than anaerobic (Tarasov et al, 2004;Kauppi et al, 2011), encouraging the addition of oxygen as a gas straight into the soil or the aquatic phase (Penttinen, 2001), or as a breakdown product of chemicals such as peroxide, persulfate, ozone or permanganate (Tarasov et al, 2004;Goi et al, 2006;Yen et al, 2011;Nykänen et al, 2012;Simpanen et al, 2016a;Bajagain et al, 2018Bajagain et al, , 2020b. The dissolvability of oxygen is comparatively low; alternatives like nitrate and sulfate sidestep this problem but come with a heightened risk of groundwater pollution (Chen et al, 2022).…”
Section: Microbial Bioremediation -Forms Prerequisites and Conditionsmentioning
confidence: 99%
“…The benefits of using nitrate as the nitrogen source are that it can also function as an electron acceptor (Kim et al, 2013;Chen et al, 2022) and is readily soluble in water as opposed to gaseous oxygen.…”
Section: Physical*mentioning
confidence: 99%
“…Such industrial waste pollutes the soil, air, surface and groundwater, and food, posing a health risk to those who are exposed. This is because these contaminants can harm many organs and systems, including the endocrine system, and thus affect their biological functions [ 4 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contamination with hydrocarbons has been associated with an increase of members belonging to Proteobacteria [10]. Chen et al ( 2022) reported some indigenous microorganisms coming from polluted groundwater or soil, such as Actinobacteria, Proteobacteria and some members of Actinomycetota such as Rhodococcus and Arthrobacter strains to have high BTEX degradation activity in their study [54]. Outcomes of this study showed that the highest relative abundance of Proteobacteria was observed in the BTEX mixture and the lowest in BTEXIeIaN.…”
Section: Microbial Composition In Different Substrate Mixturesmentioning
confidence: 56%
“…Following the argument above, we report on the iron and sulphate reducing rates found for all species, even when in this Chapter only the rates given for benzene, naphthalene, ethylbenzene (used for the lumped MAH) and 1-methyl-naphthalene (used for the lumped PAH) are used. Hydrocarbon degradation rates under iron and sulphate reducing conditions in literature vary greatly [54,184,274]. Values for the BTEX compounds were taken from a review study by Suarez and Rifai (1999) [274].…”
Section: Reactive Transport and Geochemical Responsementioning
confidence: 99%